Parietal cortex is recruited by frontal and cingulate areas to support action monitoring and updating during stopping - Jung Uk Kang; Layth Mattar; José Vergara; Victoria E. Gobo; Hernan G. Rey; Sarah R. Heilbronner; Andrew J. Watrous; Benjamin Y. Hayden; Sameer A. Sheth; Eleonora Bartoli (NeuroImage)
Summary: Recent evidence indicates that the intraparietal sulcus (IPS) may play a causal role in action stopping, potentially representing a novel neuromodulation target for inhibitory control dysfunctions. Here, we leverage intracranial recordings in human subjects to establish the timing and directionality of information flow between IPS and prefrontal and cingulate regions during action stopping. Prior to successful inhibition, information flows primarily from the inferior frontal gyrus (IFG), a critical inhibitory control node, to IPS. In contrast, during stopping errors the communication between IPS and IFG is lacking, and IPS is engaged by posterior cingulate cortex, an area outside of the classical inhibition network and typically associated with default mode. Anterior cingulate and orbitofrontal cortex also display performance-dependent connectivity with IPS. Our functional connectivity results provide direct electrophysiological evidence that IPS is recruited by frontal and anterior cingulate areas to support action plan monitoring and updating, and by posterior cingulate during control failures.